A Combination of Membrane Filtration and Raman-Active DNA Ligand Greatly Enhances Sensitivity of SERS-Based Aptasensors for Influenza A Virus - Zhdanov, Gleb; Nyhrikova, Ekaterina; Meshcheryakova, Nadezda; Kristavchuk, Olga; Akhmetova, Assel; Andreev, Evgeny; Rudakova, Elena; Gambaryan, Alexandra; Yaminsky, Igor; Aralov, Andrey; Kukushkin, Vladimir; Zavyalova, Elena (Frontiers in Chemistry, 2022)
Biosensors combining the ultrahigh sensitivity of surface-enhanced Raman scattering (SERS) and the specificity of nucleic acid aptamers have recently drawn attention in the detection of respiratory viruses. The most sensitive SERS-based aptasensors allow determining as low as 104 virus particles per mL that is 100-fold lower than any antibody-based lateral flow tests but 10–100-times higher than a routine polymerase chain reaction with reversed transcription (RT-PCR). Sensitivity of RT-PCR has not been achieved in SERS-based aptasensors despite the usage of sophisticated SERS-active substrates. Here, we proposed a novel design of a SERS-based aptasensor with the limit of detection of just 103 particles per ml of the influenza A virus that approaches closely to RT-PCR sensitivity. The sensor utilizes silver nanoparticles with the simplest preparation instead of sophisticated SERS-active surfaces. The analytical signal is provided by a unique Raman-active dye that competes with the virus for the binding to the G-quadruplex core of the aptamer. The aptasensor functions even with aliquots of the biological fluids due to separation of the off-target molecules by pre-filtration through a polymeric membrane. The aptasensor detects influenza viruses in the range of 1·103–5·1010 virus particles per ml.